2020
DOI: 10.1007/s10909-020-02347-z
|View full text |Cite
|
Sign up to set email alerts
|

KIDSpec: An MKID-Based Medium-Resolution, Integral Field Spectrograph

Abstract: KIDSpec, the Kinetic Inductance Detector Spectrograph, is a concept for a highly sensitive, medium-spectral-resolution optical through near-IR spectrograph. It uses the intrinsic-energy-resolving capability of an array of optical/IR-sensitive MKIDs to distinguish multiple orders from a low-resolution grating. By acting as an 'order resolver,' the MKID array replaces the cross-disperser in an echelle spectrograph. This greatly simplifies the optical layout of the spectrograph and enables longer slits than are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Galaxy observations also present opportunities for many different science areas. High redshift star forming galaxies and their emission lines can provide information on the stages of evolution of the universe, such as the epoch of reionisation (Onodera et al 2020). Emission line galaxies at medium to high redshifts can aid in testing the cosmological dark energy model and constrain it (Gao & Jing 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Galaxy observations also present opportunities for many different science areas. High redshift star forming galaxies and their emission lines can provide information on the stages of evolution of the universe, such as the epoch of reionisation (Onodera et al 2020). Emission line galaxies at medium to high redshifts can aid in testing the cosmological dark energy model and constrain it (Gao & Jing 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MKIDs are an exciting detector in the OPT/NIR due to being free of read noise and dark current counts, energy resolving, time resolving, and photon counting detectors. 6 In particular by using the energy resolving ability of the MKIDs, they can be used as a cross-disperser in a spectrograph, due to them being able to separate the orders falling on a linear array of MKIDs.…”
Section: Introduction 11 Microwave Kinetic Inductance Detectors and K...mentioning
confidence: 99%
“…Taking advantage of this will be the Kinetic Inductance Detector Spectrometer (KIDSpec), an upcoming medium spectral resolution OPT/NIR spectrometer. 6 While intended to have similar capabilities to X-Shooter 7 , KIDSpec will instead use MKIDs as its detectors, gaining the benefits described above. The MKIDs function as a resonant circuit made up of a capacitor and inductor.…”
Section: Introduction 11 Microwave Kinetic Inductance Detectors and K...mentioning
confidence: 99%
“…The pixel format of MKIDs in the sub-millimeter and far-infrared are also several kilopixels (Adam et al, 2018) and systems capable of reading out 10 4 pixels have been demonstrated (Baselmans et al, 2017). These large formats make MKIDs a competitive detector technology for high contrast imaging of exoplanets (Meeker et al, 2015), long slit spectroscopy (O'Brien et al, 2014), as well as security and biomedical applications (Jonge et al, 2012).…”
Section: Introductionmentioning
confidence: 99%